2019
DOI: 10.1177/2396941519845201
|View full text |Cite
|
Sign up to set email alerts
|

The earlier, the better? Diagnostic experiences of parents in a community-based early intervention system for preschool children with autism

Abstract: Background and aims In many countries, early detection and diagnosis of autism spectrum disorder is largely dependent on parents’ initial concern with early symptoms of autism spectrum disorder. Previous research on parental perceptions of the autism spectrum disorder diagnostic process indicates that parental satisfaction may be due to either the timing of the diagnostic notification or the provision of post-diagnostic support. The objective of this research is to study the diagnostic notification process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In prior years, this time lag has been reduced by improved techniques for the early detection of NDD in preschoolers (Honda et al, 2009; Jullien, 2021). In Japan, it is common for public health nurses, preschool teachers and childcare workers to recognize developmental concerns in children before parents do and to recommend that parents bring their children to see specialists for developmental assessment and diagnosis (Iwasa et al, 2019). A recent nationwide survey on ASD in Japan revealed that the cumulative incidence of ASD diagnosis in 5‐year‐old children is 2.75% and that this figure is rising (Sasayama, Kuge, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior years, this time lag has been reduced by improved techniques for the early detection of NDD in preschoolers (Honda et al, 2009; Jullien, 2021). In Japan, it is common for public health nurses, preschool teachers and childcare workers to recognize developmental concerns in children before parents do and to recommend that parents bring their children to see specialists for developmental assessment and diagnosis (Iwasa et al, 2019). A recent nationwide survey on ASD in Japan revealed that the cumulative incidence of ASD diagnosis in 5‐year‐old children is 2.75% and that this figure is rising (Sasayama, Kuge, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is sometimes difficult for parents and preschool teachers to agree on the developmental concerns of young children. Iwasa et al (2019) conducted a survey of parents' satisfaction with the process by which their children, who received early intervention before school, were diagnosed with ASD. Many of the parents were informed of developmental concerns about their child either by public health nurses at the 18‐month or 3‐year‐old health checkups or by preschool teachers or childcare workers, regardless of whether the parents had already voiced concerns.…”
Section: Introductionmentioning
confidence: 99%